Web based education game related to farming and arithmetic mathematics - Nur Anis, Mohd Khatib (2018)
Technologies nowadays has advanced so rapidly people depend on it every day. Kids these days have less exposure on farming and mathematics due to the advancement of the technologies. Furthermore, some kids have problems in learning mathematics in conventional way. Thus, web-based education game was developed to focus on solving this problem through exposing children in basic skill farming with arithmetic calculation during the farming activities. This application was developed for kids from 7 to 12 years old. This game consists of three levels; easy, intermediate and hard. All levels have specific goals to be achieved. Each level integrates the skills of farming and learning arithmetic respectively. This game was developed based on Agile by using RPG Maker MV and JavaScript language. Testing was carried out using the method of user acceptance test (UAT) and satisfaction survey. Three randomly selected users have tested the system using UAT method, based on the results, 25 out of 26 functions successfully passed the tests making the project 96% successful. Ten randomly selected users have answered the satisfaction survey and based on the results, 4 over 5 ratings were the average ratings given by them for the project. As a conclusion, this developed application able to help the kids to be exposed and gain the basic knowledge of farming and learn the arithmetic mathematics in non-conventional ways.